The pathogenesis and targeted therapies of intervertebral disc degeneration induced by cartilage endplate inflammation - Yang, Hantao; Chen, Xuandu; Chen, Jun; Dong, Yansong; Huang, Yafang; Qin, Lei; Tan, Jie; Yi, Weihong (Frontiers in Cell and Developmental Biology, 2024)
Intervertebral disc degeneration (IVDD) is the leading cause of low back pain, where degeneration and death of nucleus pulposus cells within the intervertebral disc (IVD) can be obviously revealed. This degeneration can result in an imbalance in the extracellular matrix due to the loss of proteoglycans and water content, which can further lead to catabolic and anabolic dysfunction of the IVD. Recently, the dysfunction of cartilage endplate (CEP) during aging has drawn large attention due to its essential functions in contributing nutrient exchange and maintaining IVD homeostasis. Furthermore, the inflammation and disturbed homeostasis of CEP not only accelerate the degradation of nucleus pulposus extracellular matrix, but also exacerbate IVDD by causing nucleus pulposus cell death through other pathological factors. Here in this review, we summarized the possible pathological factors and the underlying mechanisms of the CEP inflammation-induced IVDD, including exosomes degeneration, CEP calcification, ferroptosis, mechanical changes, and cell senescence. Besides, changes of miRNAs, pain-related neural reflex arc and pathways associated with CEP inflammation-induced IVDD are also reviewed. In addition, new strategies specifically designed for CEP inflammation-induced IVDD are also discussed in the last section. We hope this paper can not only offer some new insights for advancing novel strategies for treating IVDD, but also serve as a valuable reference for researchers in this field.